Variation Of Ge Concentration In Some Coniferous Species Over Long Years - Yiğit, Nurcan (Kastamonu University, 2025)
: Increasing natural events and human activities in the last century led to the release of an excessive amount of inorganic and organic pollutants into the environment and natural ecosystems. One of the most important pollutants disrupting the balance between living organisms in the ecosystem is metals. Heavy metals, in particular, are transported to the top levels of the food chain and cause harm to the living organisms. Therefore, among the pollutants, heavy metals have a specific ecological importance. Heavy metals are carcinogenic and, due to their bioaccumulative, non-degradable, and refractory characteristics, they pose serious health risks to living systems and the environment. Pinus pinaster (Pp), Cupressus arizonica (Cpa), Picea orientalis (Po), Cedrus atlantica (Cda) and Pseudotsuga menziesii (Pm) species were examined in the present study. Changes in Ge concentrations in these species by directions and organs in the periods 1988-1992 and 2013-2017 were determined. As a result of the study, the lowest Ge concentration was found in the west in the Pb (872.8) and the highest one in the north in the Cpa (6367.5). The present study revealed that Ge accumulation in the plant species analyzed here is at a considerably high level. These results suggest that Ge pollution in the air is very high.